Stunning of Nile tilapia by thermonarcosis and its effect on frozen fillets - Duarte, Rafael Severino; Santos, João Rodrigo Gil de los (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate thermonarcosis as a stunning method for Nile tilapia (Oreochromis niloticus) and its effect on the pH and total volatile basic nitrogen in the frozen fillets. For evaluation, 60 animals were divided into six temperature ranges: 0‒1ºC, 1‒2ºC, 2‒3ºC, 3‒4ºC, 4‒5ºC, and 5‒6ºC. A stunning tank with a mixture of water and ice (1:1) was used. The temperature was monitored constantly, and ice was added as needed to maintain the different temperature ranges. The fish subjected to 0‒3ºC were desensitized more quickly, in 270.3 s. There was no change in the characteristics of the fillets regarding the values of pH (6.86 to 7.00) and total volatile nitrogen bases (6.36 to 8.61 mg 100 g-1 N), both in accordance with the stipulated by the current Brazilian legislation. As a stunning method, thermonarcosis is efficient at a temperature from 0–3ºC and does not affect the quality of the frozen fillets of Nile tilapia.
Keywords: fish; desensitization; slaughter; stunning; TVB-N